2005
DOI: 10.1037/0278-7393.31.6.1459
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Contrast in Perceptual Categorization.

Abstract: People categorized pairs of perceptual stimuli that varied in both category membership and pairwise similarity. Experiments 1 and 2 showed categorization of 1 color of a pair to be reliably contrasted from that of the other. This similarity-based contrast effect occurred only when the context stimulus was relevant for the categorization of the target (Experiment 3). The effect was not simply owing to perceptual color contrast (Experiment 4), and it extended to pictures from common semantic categories (Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 37 publications
4
26
1
Order By: Relevance
“…This influence also was observed to some extent when there was a two-trial gap between the preceding and current faces. Furthermore, consistent with previous research (Hampton, et al, 2005;Stewart & Brown, 2005), these identity-based sequential effects depend on the relative distance between the preceding and current stimuli, which suggests that the local sequential context is used to inform the judgments of facial identity. Accordingly, the present study reveals that in addition to the information conveyed by the faces, facial identity is judged according to preceding contextual information.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…This influence also was observed to some extent when there was a two-trial gap between the preceding and current faces. Furthermore, consistent with previous research (Hampton, et al, 2005;Stewart & Brown, 2005), these identity-based sequential effects depend on the relative distance between the preceding and current stimuli, which suggests that the local sequential context is used to inform the judgments of facial identity. Accordingly, the present study reveals that in addition to the information conveyed by the faces, facial identity is judged according to preceding contextual information.…”
Section: Discussionsupporting
confidence: 69%
“…We probed this issue by using sequential effects. Recently, there has been a resurgence of interest in sequential effects, particularly during binary categorization processing (Hampton, Estes, & Simmons, 2005;Stewart, Brown, & Chater, 2002;Zotov, Jones, & Mewhort, 2011). In these studies, when a sequence of stimuli is presented, the categorization responses to the stimuli in current trials have been found to vary according to the local sequential context shaped by the immediately preceding stimuli presented one trial back.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies of identification and categorization conducted over the past five decades have revealed people's inability to classify or precisely estimate perceived objects independently of their preceding context (Garner, 1954;Hampton, Estes & Simmons, 2005;Holland & Lockhead, 1968;Lockhead, 2004;Medin & Schaffer, 1978;Nosofsky, 1986;Parducci, 1965;Stewart et al, 2005). These studies demonstrate that people's judgments (e.g., identification, categorization, psychophysical properties) of stimuli are strongly influenced by the corresponding aspects of preceding stimuli.…”
Section: Discussionmentioning
confidence: 99%